Local technical agro-climatic committee implementation guide: experiences from Battambang and Kampong Speu provinces in Cambodia - Soksophors, Yim; Kim, Kwang Hyung; Swaans, Cornelis P.M.; Barlis, Angelica; Phanna, Khieng (2022)
This implementation was co-produced with the project participants in Cambodia based on their own experience in piloting and implementing the Local Technical Agro-Climatic (LTAC) process, developing the final products, and disseminating the advisories through multiple communication channels to reach the end users or farmers.